Visitor experiences at UNESCO monasteries in Northeast Romania - Lupu, C.; Brochado, A.; Stoleriu, O. (Journal of Heritage Tourism, 2019)
The religious heritage of northeast Romania is one of the key attractions for visitors to the area. Known as ‘painted’ monasteries, the region’s churches highlight the rich religious culture of Romania, and they have been designated UNESCO World Heritage Sites. This study sought to identify the main dimensions of tourist experiences in the monasteries using mixed content analysis methods to collect data from Web reviews. The results include 10 themes: ‘monastery’, ‘painted (walls)’, ‘tower’, ‘visit’, ‘beautiful’ (place), ‘inside’ (painting), ‘famous’ (scene), ‘place’, ‘blue’ (colour) and ‘guide’. The Web reviews also reveal that tourists can feel connected to the Eastern Orthodox religion (e.g. most Romanian visitors) or they are more interested in the monasteries’ paintings and architecture. The majority of tourists value these structures for their status as UNESCO World Heritage Sites, seeing them as most notable for their old paintings, which have been preserved for many years and which are famed for their colours (i.e. Voronet Monastery’s blue paint).